Nursing Case Management, Peer Coaching, and Hepatitis A and B Vaccine Completion Among Homeless Men Recently Released on Parole. Issue 3 (May 2015) - Nyamathi, Adeline; Salem, Benissa E.; Zhang, Sheldon; Farabee, David; Hall, Betsy; Khalilifard, Farinaz; Leake, Barbara
<x xml:space="preserve">Abstract</x> Background Although hepatitis A virus (HAV) and hepatitis B virus (HBV) infections are vaccine-preventable diseases, few homeless parolees coming out of prisons and jails have received the hepatitis A and B vaccination series. Objectives The study focused on completion of the HAV and HBV vaccine series among homeless men on parole. The efficacy of three levels of peer coaching (PC) and nurse-delivered interventions was compared at 12-month follow-up: (a) intensive peer coaching and nurse case management (PC-NCM); (b) intensive PC intervention condition, with minimal nurse involvement; and (c) usual care (UC) intervention condition, which included minimal PC and nurse involvement. Furthermore, we assessed predictors of vaccine completion among this targeted sample. Methods A randomized control trial was conducted with 600 recently paroled men to assess the impact of the three intervention conditions (PC-NCM vs. PC vs. UC) on reducing drug use and recidivism; of these, 345 seronegative, vaccine-eligible subjects were included in this analysis of completion of the Twinrix HAV/HBV vaccine. Logistic regression was added to assess predictors of completion of the HAV/HBV vaccine series and chi-square analysis to compare completion rates across the three levels of intervention. Results Vaccine completion rate for the intervention conditions were 75.4% (PC-NCM), 71.8% (PC), and 71.9% (UC; p = .78). Predictors of vaccine noncompletion included being Asian and Pacific Islander, experiencing high levels of hostility, positive social support, reporting a history of injection drug use, being released early from California prisons, and being admitted for psychiatric illness. Predictors of vaccine series completion included reporting having six or more friends, recent cocaine use, and staying in drug treatment for at least 90 days. Discussion Findings allow greater understanding of factors affecting vaccination completion in order to design more effective programs among the high-risk population of men recently released from prison and on parole.